THE POSSIBILITY OF HYDROCARBON TRAP AND ITS POTENTIAL IN THE NORTH BONE BASIN, BASED ON GEOLOGICAL AND GEOPHYSICAL DATA - Hari P Siagian; Bambang Suci Widijono (Jurnal Geologi dan Sumberdaya Mineral, 2009)
Based on the analysis of geological and geophysical data, it can be informed that investigated area is the sedimentary Bone basin formed since the beginning of the Tertiary age and developed through Paleogen to the Neogene. The basin is defined as a fore-arc basin underlain unconformable by pre-Tertiary basement rocks comprising metamorphics, volcanics, metasediments (the Laitimojong and Pompangeo Complexes). The hydrocarbon occurrence in Bone Basin showed by gas seeps in the surface are located in Pongko and Malangke villages. Some hydrocarbon traps such as structures and stratigraphy are shown in the seismic profiles. Abundant coarse clastic and limestone deposits such as the fluviodeltaic of Toraja and Lamasi Formations may plays as good reservoir in the basin. claystone within the Lamasi Formation and shale within the Toraja Formation predicted as petroleum source rocks in the area. The seals in the basin considered as the existence of numerous claystone and siltstone horizons within the Bone Bone Formation that is also indicated by the drilling results.Â Keywords : sedimentary basin, hydrocarbon potential, trap, Bone BasinÂ